Ginseng dreams : the secret world of America's most valuable plant - Johannsen, Kristin, 1957- (University Press of Kentucky, 2006)
For thousands of years, cultures around the world have relied on herbal medicine for healing. Only recently have Americans flocked to once-suspect botanical treatments for the promise of good health and longevity. Among the most treasured of these plants is American ginseng, revered by millions of Asians as a virtual panacea that sustains every system of the human body. In Ginseng Dreams, Kristin Johannsen chronicles the remarkable world of the mysterious plant that commands as much as two thousand dollars a pound. She unfolds ginseng's history and its future through the stories of seven peop.